(untitled) (Journal of the College of Basic Education, 2022)
In order to compute impact-parameter-dependent energy losses, two extensions are needed, the orbital motion of target electrons (shell correction) need to be incorporated before instead of after integration over impact parameter, the spatial distribution of the target electrons needs to be considered. Unless stated otherwise, the term ‘shell correction’, when applied to impact-parameter-dependent energy losses, implies allowance for both the spatial and the velocity effect [1].